Invoice Discounting: A Blockchain-Based Approach - Fabrizio, Nadia; Rossi, Elisa; Martini, Andrea; Anastasovski, Dimitar; Cappello, Paolo; Candeago, Lorenzo; Lepri, Bruno (Frontiers in Blockchain, 2019)
Invoice discounting is a market with a double-digit potential growth rate in Europe and worldwide in the next years. The main beneﬁt of invoice discounting is the acceleration of cash ﬂow from customers to suppliers: suppliers get advance payments from the bank, rather than waiting for the customers to pay. Hence, thanks to the quick availability of capital, businesses can invest in expansion and growth. More speciﬁcally, one of the most relevant problems today is how to provide better and faster invoice discounting services while preventing the double spending and maintaining the risk low. The blockchain frameworks have the potential to provide the right solution and thus to revolutionize the invoice discounting process. The beneﬁts for suppliers, customers and ﬁnancial institutions are related to the increased transparency added to the whole discounting process and the following risk reduction for the banks due to the capability to enhance the entire process and to reduce the double spending. In our paper, we introduce a blockchain-based invoice discounting system, called Distributed Ledger Invoice, and we propose a novel assessment method for evaluating currently available blockchain solutions for the invoice discounting scenario. Moreover, we also discuss two main issues regarding the information accessibility and the interoperability. In particular, since blockchain is still an emerging technology interoperability is a key factor for the blockchain adoption in inter-banking processes, where different blockchains solutions might be used. In this work we propose a decoupling layer, based on the Attribute-Based Access Control language, to unify the access control to reserved information across heterogeneous blockchains.